2016
DOI: 10.1371/journal.pone.0160466
|View full text |Cite
|
Sign up to set email alerts
|

Association between Hypoalbuminaemia and Mortality in Patients with Community-Acquired Bacteraemia Is Primarily Related to Acute Disorders

Abstract: We sought to investigate whether hypoalbuminaemia was mainly caused by acute or chronic factors in patients with community-acquired bacteraemia. In this population-based study, we considered 1844 adult cases of community-acquired bacteraemia that occurred in Funen, Denmark between 2000 and 2008. We used a stepwise prognostic predisposition-insult-response-organ dysfunction (PIRO) logistic regression model by initially including age and comorbidity, then added bacterial species, and finally sepsis severity. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 45 publications
2
31
0
1
Order By: Relevance
“…Our results indicate that the sudden decline in the albumin level when bacteraemia occurs is mainly due to trans-capillary leakage, reflecting the magnitude of the microcirculation impairment. These results, together with our previous findings that the albumin level is a strong prognostic predictor [23], are clinically important. If possible for the specific patient, clinicians should focus on the day-to-day decline of albumin levels rather than albumin levels per se as such declines reflect the severity of the septic condition, which, in contrast to chronic conditions, is treatable in the acute setting.…”
Section: Epidemiology and Infection 653supporting
confidence: 83%
“…Our results indicate that the sudden decline in the albumin level when bacteraemia occurs is mainly due to trans-capillary leakage, reflecting the magnitude of the microcirculation impairment. These results, together with our previous findings that the albumin level is a strong prognostic predictor [23], are clinically important. If possible for the specific patient, clinicians should focus on the day-to-day decline of albumin levels rather than albumin levels per se as such declines reflect the severity of the septic condition, which, in contrast to chronic conditions, is treatable in the acute setting.…”
Section: Epidemiology and Infection 653supporting
confidence: 83%
“…To date, several studies have confirmed the relationship between hypoalbuminemia and delayed mortality . We found that this association is independent of other coexisting morbidities as has been recently shown in two different studies that tested the association between hypoalbuminemia, short‐term and long‐term mortality, the authors found that the correlation of hypoalbuminemia with mortality did not change after adjusting for chronic or acute conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The study cohort has been described previously [4][5][6][7]. In brief, it comprised all adult (>14 y) persons residing in the Funen County with their first-time community-acquired bacteraemia in 2000-2008, and CRP measured from two days before until the day after the bacteraemia date (date of draw of blood culture [BC]; if date of draw was missing, date of receipt of BC [never missing]).…”
Section: Derivation Of the Initial Study Cohortmentioning
confidence: 99%
“…We used logistic regression analyses with odds ratios (ORs) and 95% CIs, with mortality within 30 days from the bacteraemia date as the outcome. Initially, we adopted the predispositioninsult-response-organ dysfunction (PIRO) model [9] used previously [6]. We included age, gender,…”
Section: -Day Mortality Analysesmentioning
confidence: 99%
See 1 more Smart Citation